2019
DOI: 10.1111/cbdd.13467
|View full text |Cite
|
Sign up to set email alerts
|

Noteworthy effect of slight variation in aliphatic chain length of trisubstituted imidazole inhibitors against epidermal growth factor receptor L858R/T790M/C797S mutant in cancer therapy

Abstract: 11h is a very potent inhibitor against epidermal growth factor receptor triple mutation L858R/T790M/C797S (EGFRTM) with 13‐fold stronger potency than the FDA‐approved osimertinib. Recently, two new EGFRTM inhibitors, 11d and 11e, were reported which revealed 2.8‐ and 2.3‐fold stronger potency than 11h, respectively. 11h, 11d, and 11e have the same structures but differ only in their aliphatic chain length. However, the exact effects of differential aliphatic chain length on the inhibitory potencies of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This helps identify crucial binding site residues and their interaction patterns which would facilitate further structure‐based drug design efforts. Herein, the MM/GBSA method was used to estimate the differential binding affinities of ( R,R ) ‐ and ( R,S ) ‐7 diastereomers toward HBVC dimer (HBVCd) (Akher, Farrokhzadeh, Olotu, Agoni, & Soliman, 2019b; Akher, Farrokhzadeh, Ravenscroft, & Kuttel, 2019c; Akher, Farrokhzadeh, & Soliman, 2019a; Farrokhzadeh, Akher, Olotu, Soliman, & Van Heerden, 2019b; Farrokhzadeh, Akher, & Soliman, 2019a; Genheden & Ryde, 2012). This enabled the determination of the binding energy profiles that included other components such as electrostatic and van der Waals energies.…”
Section: Computational Methodologymentioning
confidence: 99%
“…This helps identify crucial binding site residues and their interaction patterns which would facilitate further structure‐based drug design efforts. Herein, the MM/GBSA method was used to estimate the differential binding affinities of ( R,R ) ‐ and ( R,S ) ‐7 diastereomers toward HBVC dimer (HBVCd) (Akher, Farrokhzadeh, Olotu, Agoni, & Soliman, 2019b; Akher, Farrokhzadeh, Ravenscroft, & Kuttel, 2019c; Akher, Farrokhzadeh, & Soliman, 2019a; Farrokhzadeh, Akher, Olotu, Soliman, & Van Heerden, 2019b; Farrokhzadeh, Akher, & Soliman, 2019a; Genheden & Ryde, 2012). This enabled the determination of the binding energy profiles that included other components such as electrostatic and van der Waals energies.…”
Section: Computational Methodologymentioning
confidence: 99%
“…In this study, an in-house cMD simulation protocol was employed that has been validated as previously reported. , The Amber14-integrated particle mesh Ewald molecular dynamics (PMEMD) graphical processing unit (GPU) was used to perform the cMD simulations wherein the generalized AMBER force field “leap.gaff” was used to model the inhibitor ( 20g ), and the “leaprc.ff14SB” force field, the protein biomolecules. Moreover, the covalently linked 20g -Cys797 was parametrized using the integrated Antechamber module, and the Link, Edit, and Parm (LEaP) module was used to create a library for the covalent binder.…”
Section: Computational Methodsmentioning
confidence: 99%
“…All six inhibitors belong to reversible inhibitors which are located in the cavity of the hydrophobic environment, and the location of these competitive inhibitors is the reported ATP binding site [38][39][40][41][42][43], which is involved van der Waals interactions and electrostatic interactions. It is observed that there are nearly 20 amino acids in 3.5 Å around the inhibitors from Figure S1, which are hydrophobic amino acids-Leu718, Gly719, Val726, Ala743, Met766, Leu777, Leu788, Met790, Leu792, Met793, Pro794, Phe795, Gly796, Leu844-and hydrophilic amino acids-Lys745, Cys775, Gln791, Ser797; it can be seen that the inhibitors are bounded to a large hydrophobic cavity, which is defined as "mouth" and is the same as below.…”
Section: The Binding Conformations Analysismentioning
confidence: 99%